2011
DOI: 10.1039/c0cc05408a
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal catalysed ammonia-borane dehydrogenation in ionic liquids

Abstract: Significant advantages result from combining the disparate hydrogen release pathways for ammonia-borane (AB) dehydrogenation using ionic liquids (ILs) and transition metal catalysts. With the RuCl(2)(PMe(3))(4) catalyst precursor, AB dehydrogenation selectivity and extent are maximized in an IL with a moderately coordinating ethylsulfate anion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
86
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 30 publications
3
86
0
Order By: Relevance
“…Sneddon and co-workers reported that ILs, loaded with different precious metal (Rh, Ru, Pd) or Ni-based precatalysts, decrease the onset temperature (45-85°C) of AB-decomposition significantly improving hydrogen yield at the same time ( Figure 12). (Wright et al, 2011) Figure 12. Hydrogen evolution from AB-decomposition at 65 °C catalyzed by different metal catalystprecursors.…”
Section: Ils As Solvents For Catalytic Ab Dehydrogenationmentioning
confidence: 99%
See 3 more Smart Citations
“…Sneddon and co-workers reported that ILs, loaded with different precious metal (Rh, Ru, Pd) or Ni-based precatalysts, decrease the onset temperature (45-85°C) of AB-decomposition significantly improving hydrogen yield at the same time ( Figure 12). (Wright et al, 2011) Figure 12. Hydrogen evolution from AB-decomposition at 65 °C catalyzed by different metal catalystprecursors.…”
Section: Ils As Solvents For Catalytic Ab Dehydrogenationmentioning
confidence: 99%
“…Hydrogen evolution from AB-decomposition at 65 °C catalyzed by different metal catalystprecursors. Reproduced from (Wright et al, 2011) with permission of The Royal Society of Chemistry.…”
Section: Ils As Solvents For Catalytic Ab Dehydrogenationmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of transition metal salts on this system was investigated [25]. At low temperatures these metal salts improve hydrogen yield from AB decomposition in [BMIM]Cl considerably.…”
Section: Introductionmentioning
confidence: 99%